(untitled) - Romero Léon, Consuelo C. (Wageningen, 2005)
Contents: Introduction; rainfall erosivity in the northern Andean Higlands of Peru; soil erodibility in the Northern Andean Highlands of Peru; Uncertainty analysis of WEPP; validation of the hillslope version of WEPP.
Keywords: Soil science,Khoa học đất